ACTIONS OF FINITE GROUPS ON COMMUTATIVE RINGS ANDINVARIANT IDEALS - Naoum, A.; Al-Aubaidy, Wassan (Iraqi Journal of Science, 2025)
Let R be a commutative ring with ١, and let Aut(R) denote the group of ringautomorphisms of R. We will usually consider a group G⊆ Aut(R).In this paper we will study the relation between G- invariant ideals and their traces.Also we study C.P modules and C.F modules.